The NICE alcohol misuse standard – evaluating its impact. Issue 3 (18th April 2017) - Knight, Alec; Littlejohns, Peter; Poole, Tara-Lynn; Leng, Gillian; Drummond, Colin
Abstract : Purpose: The purpose of this paper is to explore factors affecting implementing the National Institute for Health and Care Excellence (NICE) quality standard on alcohol misuse (QS11) and barriers and facilitators to its implementation. Design/methodology/approach: Qualitative interview study analysed using directed and conventional content analyses. Participants were 38 individuals with experience of commissioning, delivering or using alcohol healthcare services in Southwark, Lambeth and Lewisham. Findings: QS11 implementation ranged from no implementation to full implementation across the 13 statements. Implementation quality was also reported to vary widely across different settings. The analyses also uncovered numerous barriers and facilitators to implementing each statement. Overarching barriers to implementation included: inherent differences between specialist vs generalist settings; poor communication between healthcare settings; generic barriers to implementation; and poor governance structures and leadership. Research limitations/implications: QS11 was created to summarise alcohol-related NICE guidance. The aim was to simplify guidance and enhance local implementation. However, in practice the standard requires complex actions by professionals. There was considerable variation in local alcohol commissioning models, which was associated with variation in implementation. These models warrant further evaluation to identify best practice. Originality/value: Little evidence exists on the implementing quality standards, as distinct from clinical practice guidelines. The authors present direct evidence on quality standard implementation, identify implementation shortcomings and make recommendations for future research and practice.